Amrubicin Monotherapy for Patients with Platinum-Refractory Gastroenteropancreatic Neuroendocrine Carcinoma. (23rd June 2015) - Ando, Takayuki; Hosokawa, Ayumu; Yoshita, Hiroki; Ueda, Akira; Kajiura, Shinya; Mihara, Hiroshi; Nanjo, Sohachi; Fujinami, Haruka; Nishikawa, Jun; Ogawa, Kohei; Nakajima, Takahiko; Imura, Johji; et al.
Abstract : Objective . Patients with gastroenteropancreatic neuroendocrine carcinoma (NEC) have a poor prognosis. Platinum-based combination chemotherapy is commonly used as first-line treatment; however, the role of salvage chemotherapy remains unknown. This study aimed to analyze the efficacy and safety of amrubicin monotherapy in patients with platinum-refractory gastroenteropancreatic NEC. Methods . Among 22 patients with advanced gastroenteropancreatic NEC, 10 received amrubicin monotherapy between September 2007 and May 2014 after failure of platinum-based chemotherapy. The efficacy and toxicity of the treatment were analyzed retrospectively. Results . Eight males and two females (median age, 67 years (range, 52–78)) received platinum-based chemotherapy, including cisplatin plus irinotecan (n = 7, 70%), cisplatin plus etoposide (n = 2, 20%), and carboplatin plus etoposide (n = 1, 10%) before amrubicin therapy. Median progression-free survival and overall survival after amrubicin therapy were 2.6 and 5.0 months, respectively. Two patients had partial response (20% response rate), and their PFS were 6.2 months and 6.3 months, respectively. Furthermore, NEC with response for amrubicin had characteristics with a high Ki-67 index and receipt of prior chemotherapy with cisplatin and irinotecan. Grade 3-4 neutropenia and anemia were observed in four and five patients, respectively. Conclusion . Amrubicin monotherapy appears to be potentially active and well-tolerated for platinum-refractory gastroenteropancreatic NEC.